Shareholder litigation rights and corporate acquisitions - Chung, Chune Young; Kim, Incheol; Rabarison, Monika K.; To, Thomas Y.; Wu, Eliza (Journal of Corporate Finance, 2020)
We examine the effect of shareholder litigation rights on managers' acquisition decisions. Our experimental design exploits a U.S. Ninth Circuit Court of Appeals ruling on July 2, 1999 that resulted in a reduction in shareholder class actions. We find that, since the ruling, firms in Ninth Circuit states acquire larger targets. Furthermore, acquirers' returns are lower in these states, especially for those with weaker corporate governance. Further analysis shows that value destruction is the result of managers' freedom to conduct empire-building acquisitions using overvalued equity. Overall, our findings indicate the importance of shareholder litigation as an external governance mechanism.